Assessment of Surgical Antibiotic Prophylaxis Compliance in Pediatrics: A Pre–post Quasi-experimental Study. Issue 1 (January 2020) - Lombardi, Juliana; Nguy, Philippe; Robichaud Ducharme, Antoine; Thompson-Desormeaux, Félix; Ruo, Ni; Girard, Gabrielle; Schnitzer, Mireille E.; Thirion, Daniel J. G.; Papenburg, Jesse; Longpré, Audrey-Anne
Abstract : Objective: Data from rigorous evaluations of the impact of interventions on improving surgical antibiotic prophylaxis (SAP) compliance in pediatrics are lacking. Our objective was to assess the impact of a multifaceted intervention on improving pediatric SAP compliance in a hospital without an ongoing antimicrobial stewardship program. Study Design: A multidisciplinary team at the Montreal Children's Hospital performed a series of interventions designed to improve pediatric SAP compliance in June 2015. A retrospective, quasi-experimental study was performed to assess SAP compliance before and following the interventions. Our study included patients under 18 years old undergoing surgery between April and September in 2013 (preintervention) and in 2016 (postintervention). A 10-week washout period was included to rigorously assess the persistence of compliance without ongoing interventions. SAP, when indicated, was qualified as noncompliant, partially compliant (adequate agent and timing) or totally compliant (adequate agent, dose, timing, readministration, duration). Results: A total of 982 surgical cases requiring SAP were included in our primary analysis. The composite partial and total compliance increased from 51.4% to 55.8% [adjusted odds ratio 1.3; 95% confidence interval: 1.0–1.8; P = 0.06]. Although improvements in correct dose and readministration were significant, there was no significant improvement in correct timing, agent selection or duration. Conclusion: Our study demonstrated that overall SAP compliance did not significantly improve following a washout period, illustrating the importance of ongoing surveillance and feedback from an antimicrobial stewardship program. Our strict approach in evaluating the timing criterion may also explain the lack of a significant impact on SAP compliance. Abstract : Supplemental Digital Content is available in the text.